2015
DOI: 10.14202/vetworld.2015.221-224
|View full text |Cite
|
Sign up to set email alerts
|

Studies on incidence and evaluation of the closed medial patellar desmotomy in lateral recumbency in bovines

Abstract: Aim:The present study was conducted to find out the incidence and to evaluate the effectiveness of medial patellar desmotomy (MPD) in lateral recumbency in bovines.Material and Methods:One hundred and fifteen clinical cases of upward fixation of the patella in cattle and buffaloes were treated by closed MPD in lateral recumbency. Probable etiologies, symptoms and site of surgery including disease occurrence with respect to species, sex and season were also recorded.Results:In the present study, the highest inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
3
13
0
Order By: Relevance
“…Medial patellar desmotomy technique which is applied for treatment horses with persistent or intermittent upward patellar fixation may predispose horses to distal fragmentation of the patella due to increased stress on the middle patellar ligament [13,15] . Patellar anti-rotational suture ligaments technique can be used in these cases by using lateral condylar screw placement without patellar fragmentation risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medial patellar desmotomy technique which is applied for treatment horses with persistent or intermittent upward patellar fixation may predispose horses to distal fragmentation of the patella due to increased stress on the middle patellar ligament [13,15] . Patellar anti-rotational suture ligaments technique can be used in these cases by using lateral condylar screw placement without patellar fragmentation risk.…”
Section: Discussionmentioning
confidence: 99%
“…While stifle joint is in extension position, patella is forced to luxation. Position of the patella can be determined by antero-posterior radiographic examination [4,12,13] . Also, the trochlear groove and its shape can be assessed by a tangential view of the flexed stifle (skyline imaging technique) [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative treatments (Stashak, 2002;Brooks, 2007;Peitzmeier et al, 2015) were reported. Surgical treatments including medial patellar ligament desmotomy (MPLD) and ultrasound-guided medial patellar ligament splitting (MPLS) were presented (Turner & Mcllwraith, 1989;Stashak, 2002;Tnibar, 2002;Brooks, 2007;Madhu1 et al, 2012;Singh et al, 2015). MPLD is usually performed while the animal is standing and under the effect of sedation and local anaesthesia.…”
mentioning
confidence: 99%
“…MPL desmotomy (MPLD) and ultrasound-guided medial patellar ligament splitting (MPLS) are surgical options to treat this condition [9] [10] [12] [13] [14] [15]. MPLD is usually performed while the animal is standing and under the effect of light sedation and local anesthesia.…”
mentioning
confidence: 99%